Spiritual leadership and service performance among Chinese flight attendants: The mediating effects of meaningful work and work engagement - Lei Du; Yan Pan; Yaoliang Wu; Zixian Li; Tao Wen; Fei Gu; Ying Li; Ming Ji; Saifang Liu; Jun Zhang; Mingliang Li; Yuan Li; et al. (PLoS ONE, 2026)
As indispensable members of the flight crew for passenger transport on large aircraft, flight attendants are responsible for cabin safety, security, passenger services, and emergency response during flights. As the primary interface between passengers and airlines, their delivery of high-quality service is critical to maintaining passenger loyalty and supporting airlines’ sustained prosperity. Enhancing flight attendants’ in-flight service performance thus represents a key focus in airline management. This cross-sectional study examined the relationships among spiritual leadership, meaningful work, work engagement, and service performance using a sample of 313 Chinese flight attendants from Tibet Airlines and its branches. Psychological questionnaire surveys and correlation analyses revealed significant positive correlations among all four variables. Bootstrap analyses demonstrated that meaningful work and work engagement not only exert independent mediating effects on the relationship between spiritual leadership and service performance, but also jointly form a sequential mediating chain. Theoretical implications of these findings and practical recommendations for enhancing flight attendants’ service performance in airline management are discussed.